The Instrumentalization of the Unprivileged Combatants by Western Countries Aimed to Oppress National Liberation Wars - Abdelhamid, Fares Mahmoud Def-Allah (AUC Knowledge Fountain, 2025)
The goal of International Humanitarian Law (IHL) is purported to be the humanization of wars. Nonetheless, the atrocities committed in wars and the war criminals’ impunity suggest the failure of IHL. Notwithstanding, some voices call for reforming and developing IHL. In contrast, this thesis argues that IHL should be rejected entirely since the distinction between privileged and unprivileged combatants indicates that IHL is biased against anti-colonizers. It is biased in three senses. Firstly, IHL, particularly the distinction between privileged and unprivileged combatants, is dominated by Western rationality, which can be noticed in the domination of the civilization concept with its two oscillating logics: the logic of biology and the logic of improvement. Secondly, it legitimizes violence in favor of imperial Western states only. Non-Western states cannot make use of the IL violence. Thirdly, IHL is a fantasy. It whitewashes the more brutal branches of IL. It is also non-enforceable against war criminals from imperial Western states. The recent conflict between Palestine and Israel since October 2023 is evidence that IHL is biased in favor of Imperial powers against resistant movements. Thus, these arguments lead to a reasonable conclusion that the world would be better without IHL.